Studi Analitis Dimensi Sacifact Pendidikan Islam Pada Masa Kejayaannya (750-1258 M) - Abdul Fattah (Ulumuna, 2008)
Many islamic education institutions have emerged since the times of Prophet Muhammad. From historical perspective of classical Islam, the period of Abbasiate (750-1258) was the peak periode of their development. Applying sacifact analysis, this article is aimed at uncovering multi historical aspects of the institutions development. George Makdisi and Ahmad Syalabî have classified the development into two periods, pre-madrasah and post-madrasah. The former was considered as a milestone in the history of islamic education. The transformation proccess from masjid to madrasah went through three phases of transformation, i.e. phase of masjid, phase of masjid khân, and phase of madrasah. In addition, there were three factors accelerating the transformation process. Firstly, the educational activities in masjid were considered overlap their main function as worship building. Secondly, the need for science and knowledge emerged rapidly. And thirdly, there was new orientation in managing good education for muslim society.